Influence of social distancing on physical activity among the middle-aged to older population: Evidence from the nationally representative survey in China - Zhou, Wuping; Zhang, Lanyue; Wang, Ting; Li, Qiaosheng; Jian, Weiyan (Frontiers in Public Health, 2022)
Background Group-based physical activity is an important positive factor assisting middle-aged to older population to be regularly physical active, especially inside a society with a large population and highly sociable environment. However, when group-based physical activity has been restricted during the public health crisis including infectious disease pandemic, the influence of social distancing on physical activity among this vulnerable group need to be recognized. Objectives This study aimed to investigate the influence of social distancing on physical activity among middle-aged to older Chinese population at the national level. Methods A nationally representative social follow-up survey data (China Family Panel Studies, CFPS) for 2018 and 2020 were used. Physical activity level in year 2018 was set as baseline to be compared with that for each individual in 2020, when China implemented wide social distancing during the COVID-19. Chinese population with an age greater than 45 years were included, and three levels of physical activity were established. Logistic models were developed to identify sociodemographic characteristic that may associated with higher probability of worse PA behaviors during the social distancing. Results Over 46% respondents could be described as being Physically Inactivity during 2018 and this proportion increased to 67.2% in 2020. Respondents who living in the Northeast or rural regions, having a spouse, being in employment, having a low level of education and being of low-income level showed a higher decrease in physical activity compared to other group. However, individuals living with chronic diseases emerge as being more likely to maintain positive habits with respect to physical activity in this context. Conclusion Social distancing during the COVID-19 pandemic have significantly influenced the extent of physical activity among middle-aged to older Chinese. This is especially true in respect of middle-aged to elderly people who are at increased risk of chronic diseases. Given this, there is a clear need to consider effective modalities for physical activity in the context of social distancing based on home quarantine and city lockdown. Furthermore, specific health-related strategies need to be considered in relation to different regions and populations.